Kiai's National Politics in developing Moderate Santri - Wijaya, Mirza Mahbub; Nurchamidah (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2024)
This article discusses the role of Islamic scholars (kiai) in cultivating the values of national politics to shape moderate Santri. Confronting the phenomenon of Islamic scholars involved in political contests, both actively and those choosing to remain neutral, this article outlines how kiai plays a role in imparting the values of national politics and analyzes the impact of internalizing these values on Islamic students. Utilizing a qualitative method and a phenomenological approach, the findings in this article highlight the significance of the kiai's role in developing political awareness and patriotism among Islamic students, ultimately contributing to the construction of a better and more just society. The research also notes that the political stance of the kiai is not always reflected in practical political contests; the silence of the kiai regarding external influences can also be considered a political strategy. The national political orientation of the kiai is also manifested through Sufi-influenced actions in society and adaptive attitudes towards local culture